EFEKTIVITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN MELALUI APLIKASI SILOKA (SISTEM LAYANAN ONLINE KEPENDUDUKAN) DI KABUPATEN BOGOR - Cristian Nicodemus Barus; Puji Astuti (Journal of Politic and Government Studies, 2025)
This research is motivated by the digital transformation of population administration services in Bogor Regency through the SILOKA application (Online Population Service System) launched by the Population and Civil Registration Office of Bogor Regency in 2020, although various public complaints regarding technical issues and accessibility are still found, so its effectiveness needs to be assessed. This study aims to analyze the effectiveness of population administration services through the SILOKA application and identify obstacles in its implementation. In evaluating the effectiveness of this digital service, this study employs the E Service Quality theory by Parasuraman, Zeithaml, and Malhotra (2005), which encompasses seven dimensions: efficiency, reliability, fulfillment, privacy, responsiveness, compensation, and contact. The research employs a quantitative approach with 100 respondents from the people of Bogor Regency who have used SILOKA, selected through accidental sampling technique, and analyzed using validity tests, reliability tests, the SERVQUAL method, and Importance Performance Analysis (IPA) with a Cartesian diagram. The results show that The service effectiveness of the Siloka application is asymmetrical regarding Management and Human Resources, as evidenced by the Privacy, Responsiveness, and Compensation indicators, which are consistently situated in Quadrant B (keep up the good work). The personnel have demonstrated a high commitment to service and are proactive in providing information whenever system disruptions occur. Conversely, the primary obstacle lies in the Information Technology Infrastructure aspect, as reflected by the Reliability indicator, which falls into Quadrant A (top priority) with the largest negative Gap value. This infrastructure failure serves as the main barrier, where inadequate server capacity and bandwidth result in the application frequently experiencing errors, network disruptions, and the malfunction of features that are crucial for the public. This study recommends the structuring and maintenance of information technology infrastructure, the provision of an integrated complaint channel, the implementation of system-based technical supervision, and periodic public satisfaction evaluations to the Population and Civil Registration Office of Bogor Regency.